Spontaneous intracerebral haemorrhage: a rare complication of aortic aneurysm endoleak. (23rd June 2018) - Kerr, Neal; Kerr, Jasmin; Faed, James M; Krysa, Jo
Abstract : We present a rare case of intracerebral haemorrhage secondary to consumptive coagulopathy in relation to ongoing endoleak after thoracic endovascular aneurysm repair (TEVAR). A 68-year-old man underwent elective TEVAR for an 18 cm diameter Crawford type II thoracoabdominal aneurysm. He was subsequently shown to have a type 1b endoleak and a short episode of disseminated intravascularcoagulation (DIC) perioperatively. Two months after the procedure, he experienced a consumptive coagulopathy leading to intracerebral haemorrhage and ultimately his death. Endoleak-related DIC is an underappreciated phenomenon within the medical literature. Currently, management is reliant on general DIC principles and anecdotal experiences of others within the case report literature.